ANALISIS KESALAHAN SISWA MEMECAHKAN MASALAH BEDASAKAN PENELITIAN POLYA MATERI KALOR SMP - Yuniarti, Robicca; Tandililing, Edy; Arsyid, Syaiful B (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe objectives of this research are to find out the errors and the sources of errors. The research was conducted at Senior High School 2 Pontianak with 33 students as the subject. The data collected through essay and interview. Essay was taken to find out the errors, while interview was conducted to find out the sources of errors. Technique analysis of miles and Huberman was used on the data. The result shows that students’ errors were divided into 4 errors based on Polya’s problem-solving stages. (1) Errors in understanding the problem is 29.7%. Errors was happened due to the lack of conscientious and lack of practices to write down what students know and what students should ask. (2) Errors in planning the solution is 38.8%. The source of errors were due to students’ less experienced in formulating equation and its steps. (3) Difficulties in executing the plan is 55.14%. The source of this errors was the student unable to finish the test based on the plan, thus the student were not able to reach the conclusion. (4) Difficulties in recheck or double check is 49.7%. The sources of errors were miscalculation that caused the students to lost track of the test and made the recheck harder. Keywords : Analyzed of Mistake, Problem Solving based on Polya, Energy and Heat Movement